THE IMPACT OF OVERALL QUALITY AND SELF-EFFICACY ON CONATIVE USE WITH USER'S SATISFACTION AS A MEDIATION VARIABLE - Kusuma G.D.; Rosidi; Iqbal S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
The Ministry of Finance of the Republic of Indonesia built a web-based integrated system called the Agency Level Financial Application (SAKTI) to provide benefits: increased integration, efficiency, planning, implementation and accountability of the state budget. This study aims to determine and explain user satisfaction as a mediating variable for the causal relationship between overall quality and self-efficacy towards conative use of information systems. SAKTI users were a primary data that collected directly by distributing questionnaires. The questionnaire includes overall quality, self-efficacy, user satisfaction and conative use. This research focuses on the central work unit of the Ministry of Public Works and Public Housing. The population in this study were 552 people. The sampling technique used in this study was stratified random sampling consisting of 3 levels of users: operators, validators and approvers with a total of 247 respondents. Most respondents were male with a total of 125 people or 50.6%, while female were 49, 4%. In addition, most of the respondents have a bachelor's degree (131 people or 53%). Data analyzed using Structural Equation Modeling (SEM) - Partial Least Square (PLS). The findings show that overall quality and self-efficacy have a direct and independent effect on conative use of SAKTI. The results of this study also examine the relationship between overall quality, self-efficacy and conative use through user satisfaction.